Analisis Manajemen Program Bahasa Inggris Kelas Unggulan di Madrasah Ibtidaiyah - Suttrisno, Suttrisno; Istiani, Nurul; Habibulloh, M. Romadlon (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This study aims to determine the management of the superior class English program at MI Islamiyah Ngasem. This type of research is qualitative research, using a qualitative descriptive approach, which is used to describe the application of management functions in the superior class English program at MI Islamiyah Ngasem. Data collection techniques are interview, observation and documentation techniques. The results of this study indicate that the management of the superior class English program at MI Islamiyah Ngasem has been carried out properly and correctly starting from planning, organizing, implementing and supervising. The English learning strategies used in each class are varied, and use games on certain materials. Learning is packaged creatively and attractively but still focused on memorizing vocabulary. Constraints faced by the program consist of the limited, lack of student motivatitheon, the inability of parents in terms of financing and the environment. While the supporting factor is the full support of the foundation and the madrasa committee, competent teachers and high interest from parents